Organizing Production Processes in the Construction Materials Industry Based on Quality Management Principles - Achilov Ilmurad Nematovich (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The acceleration of globalization and intensification of competition in industrial sectors have positioned product quality as a key determinant of market position and long-term development prospects, particularly in the construction materials industry where quality directly affects public safety and structural reliability. Specific Background: The construction materials industry represents a technologically complex, multi-stage system requiring strict adherence to technological regimes, yet traditional management approaches focus primarily on finished product inspection rather than addressing root causes of quality deficiencies. Knowledge Gap: While foreign scholars have extensively addressed theoretical foundations and universal models of quality management, and domestic researchers have examined technological and standardization aspects, the comprehensive organization of production processes in the construction materials industry based on quality management principles remains insufficiently systematized. Aims: This study provides a comprehensive analysis of organizing production processes in the construction materials industry through quality management principles, examining theoretical foundations, scientific approaches, practical state, and recent statistical data to develop specific practical recommendations. Results: The research demonstrates that implementing quality management systems—including ISO 9001 standards, statistical quality control methods, and process-based approaches—stabilizes quality indicators, optimizes production costs, and enhances competitiveness while positively impacting environmental sustainability and social responsibility. Novelty: This study systematically integrates quality management principles with resource efficiency and environmental requirements as essential components of sustainable production organization in construction materials enterprises. Implications: The findings confirm that quality-oriented management strengthens enterprise positions in domestic and international markets, enhances investment attractiveness, and constitutes a critical direction for ensuring sustainable development of the construction materials sector and national economic competitiveness.Keywords : Quality Management Systems, Construction Materials Industry, Production Process Organization, ISO 9001 Implementation, Statistical Quality ControlHighlight : Process-based quality control reduces defects more effectively than traditional post-production inspection methods. Statistical analysis integration enables forecasting of quality variations in cement and concrete manufacturing. ISO 9001 implementation requires strategic alignment and active management involvement beyond documentation compliance.